Evidence-informed innovation in schools: aligning collaborative research and development with high quality professional learning for teachers. Issue 2 (2017) - Greany, Toby; Maxwell, Bronwen
Innovation efforts in schools commonly wrestle with two challenges: how to secure ownership of change among teachers and how to ensure that improvements are based on evidence. This paper draws on findings from a two-year collaborative research and development (R&D) project in England which involved 66 school clusters (teaching school alliances (TSAs)) in implementing and evaluating school-based innovations and a separate umbrella review of evidence on effective continuous professional development and learning (CPDL) for teachers. We find that collaborative R&D can enhance the ownership of change among participating teachers and ensure that innovations are based on evidence. We define a framework for integrating R&D and CPDL which could enable evidence-informed improvement to be scaled up, impacting on all staff. Drawing on Winch et al.'s (2015) model of teachers' professional knowledge we argue that the proposed framework could enhance the potential for teaching to be accepted as an "evidence-informed professional endeavour".